Effect of acupuncture on stress responses in equine athletes submitted to dressage - Villas-Boas, Julia Dias (2018)
Horses have a natural predisposition for sport, however, their use in competitions can result in stress-related problems that impair their sporting performance and especially their health. Thus, the use of strategies that can prevent or minimize the deleterious effects of stress is essential. In this sense, acupuncture is an ancient technique of Traditional Chinese Medicine that has been used in the treatment and prevention of stress-related diseases. Therefore, we evaluated whether acupuncture can alter stress responses in horses submitted to a dressage test. Six Brasileiro de Hipismo horses, aged between 6-8 years old, used for dressage training, from Army Riding School, Rio de Janeiro, Brazil were used. The effect of acupuncture at points GV1, HT7, GV20, and B52 immediately before to the dressage was evaluated through analysis of test performance, serum cortisol and heart rate variability (HRV). Polar Equine ™ heart rate monitor was used for HRV analysis and blood samples were collected before and 30 minutes after the end of the dressage. The performance was judged by official judges and by the riders. Acupuncture significantly reduced the LF / HF ratio (p < 0,0001), an index that indicates the sympathovagal balance suggesting that acupuncture can reduce the cardiac autonomic response in stressful situations. However, acupuncture had no effect on heart rate, cortisol levels and performance assessed by judges and riders. Our results suggest that acupuncture may reduce some stress responses in horse athletes submitted to dressage and that this effect can be related to its potentiating action of vagal activity